2021
DOI: 10.1302/0301-620x.103b.bjj-2020-1862.r1
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus infection in hip fractures (CHIP) study

Abstract: Aims Despite the COVID-19 pandemic, incidence of hip fracture has not changed. Evidence has shown increased mortality rates associated with COVID-19 infection. However, little is known about the outcomes of COVID-19 negative patients in a pandemic environment. In addition, the impact of vitamin D levels on mortality in COVID-19 hip fracture patients has yet to be determined. Methods This multicentre observational study included 1,633 patients who sustained a hip fracture across nine hospital trusts in North We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
2
5
1
Order By: Relevance
“…The 30-day mortality of 29.4% identified within this study is comparable with published literature in the UK (range from 16.3% to 35.6%),15–17 19 34 41 Italy (18.75%),14 Spain (30.4%)13 and the USA (range from 35.3% to 56%) 18 20. From a study within the UK, the authors also found a correlation between male sex and increased mortality (OR 2.69), which is similar to that demonstrated in this study (OR 2.29) 16.…”
Section: Discussionsupporting
confidence: 88%
“…The 30-day mortality of 29.4% identified within this study is comparable with published literature in the UK (range from 16.3% to 35.6%),15–17 19 34 41 Italy (18.75%),14 Spain (30.4%)13 and the USA (range from 35.3% to 56%) 18 20. From a study within the UK, the authors also found a correlation between male sex and increased mortality (OR 2.69), which is similar to that demonstrated in this study (OR 2.29) 16.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, our regional audit identified a possible association between vitamin D deficiency and mortality in COVID-19 positive hip fracture patients [11]. However, the results of this larger national observational study have not found any association between vitamin D deficiency and 30day mortality in this cohort of patients.…”
Section: Discussioncontrasting
confidence: 54%
“…Our previous regional audit carried out in Merseyside, UK, showed a potential association of decreasing vitamin D levels and increasing mortality in a hip fracture population. The study sample, however, was small and any potential association did not reach statistical significance [11]. Given previous publications which reported mixed results, the findings of our earlier regional audit, and the potential for cost effective intervention, there is a strong rationale to study if vitamin D deficiency is associated with higher mortality in COVID-19 infections.…”
Section: Introductionmentioning
confidence: 77%
“…It has even been hypothesized that vitamin D deficiency for COVID-positive hip fracture patients may contribute to increased mortality. 34 …”
Section: Discussionmentioning
confidence: 99%